1990
DOI: 10.1002/jbmr.5650050714
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin as an inhibitor of cartilage metabolism: Effect on avian chondrocyte proliferation in cell culture

Abstract: Elevated levels of bilirubin and other tetrapyrroles are common to a number of chronic hematologic and liver diseases that can result in growth failure. This report establishes a cellular model system for the study of these endogenous growth inhibitors. Primary chondrocyte cultures were prepared from embryonic chick cartilage; cells were incubated (0.3 X 10(5) cells per plate) in tissue culture medium containing 10% fetal bovine serum (FBS) with or without added bilirubin, 0.01-0.10 mM. Bilirubin caused profou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Thus, as observed by Janes et al, the presence of sera with a high concentration of bilirubin resulted in decreased cell viability 5. Moreover, depression of proliferation of other cells of calcifying tissues by bilirubin has also been reported 21. The current study, however, adds new information, because reduced osteoblast viability was observed with sera samples from jaundiced patients, particularly in the experiments performed with the highest bilirubin concentration in culture media (66 μM).…”
Section: Discussionsupporting
confidence: 68%
“…Thus, as observed by Janes et al, the presence of sera with a high concentration of bilirubin resulted in decreased cell viability 5. Moreover, depression of proliferation of other cells of calcifying tissues by bilirubin has also been reported 21. The current study, however, adds new information, because reduced osteoblast viability was observed with sera samples from jaundiced patients, particularly in the experiments performed with the highest bilirubin concentration in culture media (66 μM).…”
Section: Discussionsupporting
confidence: 68%
“…observed that plasma with high concentrations of bilirubin resulted in decreased human osteoblast-like cells proliferation [19]. Similarly, bilirubin induced a marked dose-dependent inhibition of avian chondrocytes proliferation [20].…”
Section: Discussionmentioning
confidence: 97%
“…observed that plasma with high concentrations of bilirubin resulted in decreased human osteoblast-like cells proliferation [19]. Similarly, bilirubin induced a marked dose-dependent inhibition of avian chondrocytes proliferation [20]. Previous studies from our group have shown a decrease of human osteoblastic cells viability and differentiation when bilirubin and sera from jaundiced patients was added to the culture media [7].…”
Section: Discussionmentioning
confidence: 99%